Emergence of new systematics for open charm production in high energy collisions - Braun-Munzinger, Peter; Redlich, Krzysztof; Sharma, Natasha; Stachel, Johanna (Journal of high energy physics, 2025)
We present the production systematics of open charm hadron yields in highenergy collisions and their description based on the Statistical Hadronization Model of charm (SHMc). The rapidity density of D0, D+, D∗+, D+s mesons and Λ+c baryons in heavy ion and proton-proton collisions is analyzed for different collision energies and centralities. The SHMc is extended to open charm production in minimum-bias and high-multiplicity pp collisions. In this context, we use the link established in [ 1, 2 ], between the rapidity density of open charm hadron yields, dNi/dy, and the rapidity density of charm-anticharm quark pairs, dNc¯c/dy. We demonstrate that, in pp, pA and AA collisions, dNi/dy scales in leading order with dNc¯c/dη and for open charm mesons, D0, D+ and D∗+ the slope coefficient is quantified by the appropriate thermal density ratio calculated in the SHMc at the chiral crossover temperature, Tc = 156.5 MeV. The slope coefficient for dNΛ+ c /dy differs at Tc by a factor of 1.97 ± 0.14 which is attributed to missing charmed-baryon resonances in the PDG. It is also shown that dNi/dy exhibits power-law scaling with the charged-particle pseudo-rapidity density in high energy collisions and within uncertainties. Furthermore, presently available data on different ratios of open charm rapidity densities in high-energy collisions are independent of collision energy and system size, as expected in the SHMc.
Gesehen am 08.10.2025